Investigating filopodia formation on fibronectin and cadherin substrates - Vaitkeviciute, Monika (My University, 2023)
Cancer metastasis involves cancer cells migrating from primary tumours to distant organs and tissues. Filopodia, slender finger-like protrusions, play a pivotal role in cell migration and interactions with the extracellular matrix (ECM) and neighboring cells. While filopodia formation during cell-ECM interactions has been extensively studied, our understanding of filopodia formation during cell-cell interactions remains limited. Despite extensive research on focal adhesions and adherens junction-associated proteins, the functions of certain proteins remain unknown. Cerebral Cavernous Malformations 3 protein (CCM3) is one such protein found at both focal adhesions and adherens junctions. Preliminary data from the lab indicates that CCM3 can also localize at filopodia tips, suggesting a potential role in filopodia formation and regulation. However, the specific mechanisms and effects of CCM3 on filopodia remain unknown. This study investigated filopodia formation and dynamics on fibronectin and cadherin substrates, representing cell-ECM and cell-cell interactions, respectively. We also explored the function of CCM3 in filopodia formation and regulation. Confocal spinning disk microscopy and confocal microscopy with AiryScan were used to evaluate filopodia properties and dynamics in fixed and live samples, respectively. Results showed that cells on fibronectin spread more but formed fewer filopodia than cells on cadherins. Live imaging revealed heightened filopodia dynamics on cadherin substrates compared to fibronectin. Inhibition of CCM3 had no significant impact on filopodia number or dynamics, although a notable increase in cell area was observed on fibronectin. These findings enhance our understanding of cell-cell and cell-ECM interactions critical for filopodia-mediated processes, such as cancer cell migration.
Keywords: filopodia, cadherin, fibronectin, CCM3